2022
DOI: 10.1155/2022/1836597
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Heavy Metals in Rice (Oryza sativa. L) Grains Cultivated in Three Major Industrial Areas of Bangladesh

Abstract: Human exposure to nonessential trace elements occurs from food crops that are contaminated by the soil. The present study aimed to determine the level of heavy metals in soil and rice samples using an atomic absorption spectrophotometer from three major industrial areas in Bangladesh: Savar, Gazipur, and Ashulia. Heavy metals were detected in the order Fe > Zn > Ni > Cr > Pb > Co > Cu > Cd > As and Zn > Cu > Cr > Co > Fe > Cd > Pb > Ni > As in the soil and rice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
2
12
5
Order By: Relevance
“…Toxic metal exposure, e.g., lead, via food intake has been a public health concern for decades. The lead content in rice plants has been reported previously in China, Pakistan, Thailand, Bangladesh, and Indonesia [1][2][3][4][5][6]. It was reported that lead was stored up in the order of root > stalk > leaf > grain of the rice plants [2].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Toxic metal exposure, e.g., lead, via food intake has been a public health concern for decades. The lead content in rice plants has been reported previously in China, Pakistan, Thailand, Bangladesh, and Indonesia [1][2][3][4][5][6]. It was reported that lead was stored up in the order of root > stalk > leaf > grain of the rice plants [2].…”
Section: Resultsmentioning
confidence: 94%
“…However, the paddy fields located near industrial areas and highways are easily contaminated by heavy metals. Previous studies carried out in China, Pakistan, Thailand, Bangladesh, and Indonesia, have reported the heavy metals content in rice [1][2][3][4][5][6]. Lead is harmful when its amounts are higher than the optimum.…”
Section: Introductionmentioning
confidence: 99%
“…Energy-dispersive X-ray spectroscopy (EDX) may be incorporated in an advanced cutting-edge SEM setup to analyze the atomic composition of the sample surface. The concurrent application of SEM and EDX reveals the size, shape, surface texture, and the factors present in a notably short duration [18].…”
Section: Morphology Of Explosible Dustmentioning
confidence: 99%
“…Several researchers have conducted some efforts in the health risk assessment of HMs in the crops and their rhizosphere soils [5][6][7]. Haghnazar et al [5] evaluated the Minerals 2023, 13, 629 2 of 18 HM pollution in paddy and rice grains in the Zarjoub and Goharroud river basins in northern Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is of the higher bioaccumulation at both locations and the hazard index value for wild rice seeds from both sites was high. Anwarul Hasan [7] examined the level of heavy metals in soil and rice samples in Savar, Gazipur and Ashulia (Bangladesh). The order of heavy metals in the soil and rice samples was Fe > Zn > Ni > Cr > Pb > Co > Cu > Cd > As and Zn > Cu > Cr > Co > Fe > Cd > Pb > Ni > As, respectively.…”
Section: Introductionmentioning
confidence: 99%